Evaluasi Ketersediaan Air Baku Di Kecamatan Anggeraja : Studi Kasus PDAM Tirta Massenrempulu, Kabupaten Enrekang - Gaffar, Farida; Aziz, Indriyanti; Antaria, Sukmasari; Marwa; Hasmina (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
PDAM Tirta Massenrempulu is the main provider of piped clean water by utilizing river and spring water as its main water source. Anggeraja sub-district experiences an increase in population every year so that the demand for raw water also increases. Therefore, discharge data is essential for managing the available water resources. The purpose of this study is to analyze the availability and demand of raw water in Anggeraja Sub-district using the FJ Mock method. Based on the results, it was found that the availability of raw water can meet the needs of the population in Anggeraja District. For instance, the projected water availability in 2034 is 74.46 m³/second. Meanwhile, the comparison between water availability and demand over the next 20 years shows a continuous increase in demand. In 2024, the available raw water is 36.65 m³/second, and by 2034, the demand rises to 66.46 m³/second. Thus, the water balance indicates a surplus, with an excess of 37.90 m³/second in 2024 and 7.90 m³/second in 2043.